Identifying compassionate oesophago-gastric cancer service care: a qualitative exploratory study of patient experiences and expectations in England - Simon Parsons; Christopher Bailey; Louise Bramley; Alison Cowley; Joanne Margaret Cooper; Anne Sims; Sevim Y Hodge (BMJ Open)
Objectives Oesophago-gastric cancer is one of the most common causes of cancer death worldwide. Care pathways are highly variable and complex to organise;however,there is limited evidence from a service user perspective to inform service design for best experience of care. This study explored the experiences of people living with incurable oesophago-gastric cancer to determine how services can be delivered to best support their needs.Design Based on interpretivism, this qualitative study used single, face-to-facesemistructured interviews. Interviews were audiorecorded and transcribed verbatim by a professional transcription serviceandinterrogated throughframework analysis.Setting and participants The study was based in a large UKNational Health ServiceTrust and designated regional specialist cancer centre. A total of27 patientsliving with incurable oesophago-gastric cancer took part in the study.Results The analysis revealed a central theme of‘integrated relationship-centred care’and three subthemes: compassionate care interactions, integrated processes and systems and compassionate care environments. Positive experiences were marked by high-quality relationships with healthcare professionals, further strengthened by care process and environments that responded to their individual symptoms and healthcare needs, effectively spanning multiple agencies and professions.Conclusions High quality services require enhanced clinical awareness and integrated service design to address a range of physical and psychosocial challenges which are often overlooked in thispatientpopulation. These essential components of positive care experiences must be driven at policy level to ensure a pathway approach to quality relationship-centred care, which crucially is not interrupted aspatientsmove across organisations and systems.